2013
DOI: 10.1007/s11128-013-0654-1
|View full text |Cite
|
Sign up to set email alerts
|

A universal quantum circuit scheme for finding complex eigenvalues

Abstract: We present a general quantum circuit design for finding eigenvalues of non-unitary matrices on quantum computers using the iterative phase estimation algorithm. In addition, we show how the method can be used for the simulation of resonance states for quantum systems.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…In Ref. [42,43], a general circuit design consisting of 2log 2 N qubits and O(N 2 ) quantum gates is given for the simulation of a matrix of order N not necessarily Hermitian. In particular, it is shown that any matrix can be simulated on certain predetermined states by using log 2 N ancilla qubits.…”
Section: F Possible Applicationsmentioning
confidence: 99%
“…In Ref. [42,43], a general circuit design consisting of 2log 2 N qubits and O(N 2 ) quantum gates is given for the simulation of a matrix of order N not necessarily Hermitian. In particular, it is shown that any matrix can be simulated on certain predetermined states by using log 2 N ancilla qubits.…”
Section: F Possible Applicationsmentioning
confidence: 99%
“…Some work has been done on this track to solve the resonance problem by quantum computers. By designing a general quantum circuit for non-unitary matrices, Daskin et al [36] explored the resonance states of a model non-Hermitian Hamiltonian. To be specific, he introduced a systematic way to estimate the complex eigenvalues of a general matrix using the standard iterative phase estimation algorithm with a programmable circuit design.…”
Section: Excited States and Resonancesmentioning
confidence: 99%
“…Then by complex-scaling method, the internal coordinates of the Hamiltonian is dilated by a complex factor η = αe −iθ such that H(x) → H(x/η) ≡ H η (x). We can solve the complex eigenvalue of H η (x) by the method D or using our previous method [36].…”
Section: Excited States and Resonancesmentioning
confidence: 99%
“…where the first part of the matrix is equal to H with/without some normalization, and a • indicates another part of the matrix. As also mentioned in the introduction, these types of matrices are used in various contexts: either to design quantum circuits from matrix elements [11,12] or to be able to use it with the oblivious amplitude amplification [14], or to estimate unitary dynamic of a Hamiltonian through truncated Taylor series [13] and its generalized form [15].…”
Section: Proposed Eigenvalue Estimationmentioning
confidence: 99%
“…A quantum operator (or a dynamic of a system) can be implemented inside a larger system, where some reduced part of the system represents the action of the original system. This idea is used in different contexts such as designing circuits from matrix elements [11,12], and generating exponential of a matrix written as a sum of unitary matrices through Taylor series [13]. Moreover, in Ref.…”
Section: Introductionmentioning
confidence: 99%